EDUCATIONAL MANAGEMENT OF THE ARAB REPUBLIC OF EGYPT - Lukman Asha (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Empirical research oriented to contextual issues has dominated research in the field of education management science. Academics in educational management, however, require scientific information from a bibliometric research genre, such as normative research. Thus, this study employd the concept of bibliometric research realized into normative research, with the goal of portraying the educational management of the Arab Republic of Egypt. This research served as a reflective and comparative material for academics in the field of educational management. Using the Google Scholar platform, this study was able to gather 60 scientific sources in the form of journal articles, books, and university research on the raised issu. Using the inter-coder reliability technique, this study reduced the 60 sources to 22 sources based on the criteria considered to be the most relevant and substantial sources with regard to the issue. In addition, data analysis was carried out using an interactive model. The normative research findings divided the discussion into six sub-themes under the umbrella theme, the so-called Egypt's education management, namely authority; funding; personnel; curriculum and teaching methodology; exams, class continuity, and certifications; and educational evaluation and assessment.